A myxovirus resistance like protein involved in CgIFNLP mediated immune response of oyster Crassostrea gigas. Issue 119 (December 2021) - Li, Yuanmei; Qiao, Xue; Liu, Zhaoqun; Wang, Lingling; Song, Linsheng
Abstract: The myxovirus resistance (Mx) proteins belong to interferon (IFN)-induced dynamin GTPase and play a pivotal role in the inhibition of replication of numerous viruses. In the present study, an Mx homologue (designated as Cg Mx1) was identified from oyster Crassostrea gigas . The open reading frame (ORF) of Cg Mx1 cDNA was of 1689 bp encoding a peptide of 562 amino acid residues. There was an N-terminal dynamin GTPase domain in the predicted peptide, which consisted of a tripartite GTP-binding motif (GDXXSGKS, DLPG and T/NKXD). The deduced amino acid sequence of Cg Mx1 shared 30–39% similarity with other Mx family members. And Cg Mx1 was clustered with Mx from H. discus, and then assigned into the invertebrate branch of the phylogenetic tree. The mRNA transcripts of Cg Mx1 were constitutively distributed in all the tested tissues, with the highest level in haemocytes (1342.45-fold of labial palps, p < 0.05). The mRNA expression of Cg Mx1 in haemocytes was significantly up-regulated to the highest level at 6 h (13.14-fold, p < 0.001) after poly (I:C) treatment and at 24 h (66.28-fold, p < 0.001) after recombinant IFN-like protein (r Cg IFNLP) stimulation, respectively. Cg Mx1 protein was found to distribute in both the cytoplasm and nucleus of haemocytes. In the oysters with Cg IFNLP and signal transducer and activator of transcription ( Cg STAT) silenced by RNAi, the mRNA expression of Cg Mx1 decreased significantly in the haemocytes at 12 h after poly (I:C) stimulation, which was 0.02-fold and 0.04-fold of that in EGFP-RNAi oysters ( p < 0.001), respectively. Meanwhile, EMSA assay revealed that Cg STAT was able to transactivate Cg Mx1 promoter through directly binding to its interferon-stimulated response element (ISRE) and gamma interferon activation site (GAS). The above results indicated that Cg Mx1 participated in the immune response of C. gigas through the signal pathway mediated by Cg IFNLP and Cg STAT. Highlights: A novel Cg Mx1 was identified from C. gigas with conserved domain characteristics. Cg Mx1 widely distributed in oyster tissues and responded to poly (I:C) and r Cg IFNLP stimulation in haemocytes. Cg STAT could transactivate the Cg Mx1 promoter through direct binding to the ISRE and GAS sites in vitro. Cg Mx1 could be regulated by Cg IFNLP and Cg STAT.